The Role of Healthcare Workers in Promoting Adherence to Infection Control Measures During Pandemics: A Systematic Review. - Khulayf Alanazi, Ahmed Mutlaq; Salamah Alhazmi, Bassam Omar; R Alzahrani, Hatem Abdullah; Alashjaee, Tariq Khalaf Nadi; Sameer Almotere, Abdullaziz Abdullah; Al Sulayyim, Faisal Ali Mahdi; Hawil Alharbi, Mohammed Muhza; Saud Alharbi, Hadlan Mufadhi; Saeed Alahmari, Dhafer Mohammed; M Alshammari, Mathoud Mamdouh (Journal of Neonatal Surgery, 2025)
Introduction: Healthcare workers (HCWs) play a crucial role in preventing infections during a pandemic, but the alarming rates of occupational infections (19.1% MERS, 12.5% COVID-19) in Saudi Arabia (KSA) reflect a very high failure rate of infection prevention and control (IPC) adherence. Objective of Study: The purpose of this systematic review is to critically examine and appraise the current evidenced-based knowledge on healthcare workers (HCWs) facilitating adherence to infection control measures (ICMs) during pandemics, in particular within healthcare settings in Saudi Arabia. Research Methods: This systematic review integrated studies out of KSA, focusing on compliance differences across profession (nurses and physicians), barriers to adherence (workload, inadequate resources), and the effectiveness of multicomponent interventions. The data in this review also captures adherence to the interventions resulting in a reduction of Healthcare Associated Infections (HAIs). Conclusion: Although we found moderate IPC adherence, the adherence rates for HCWs working in institutions, was influenced due to high workloads, and inadequate staffing, and reflected a general gap in compliance with nurses in practice, as compared to physicians. Multicomponent intervention strategies are useful and effective in increasing hand hygiene compliance (from 50.17% to 71.75%) while also demonstrating a solid negative correlation in HAI rates. Overall, the study found that HCW adherence may be one of the strongest contributors, while still needing structure and support, on patient safety and the need for ongoing tailored education.